Determinants of Pregnancy-Induced Hypertension among Mothers Attending Public Hospitals in Wolaita Zone, South Ethiopia: Findings from Unmatched Case-Control Study - Yitagesu Belayhun; Yibeltal Kassa; Niguse Mekonnen; Wakgari Binu; Mahilet Tenga; Bereket Duko (International Journal of Hypertension)
Background. It has been estimated that approximately 14% of maternal death has resulted due to pregnancy-induced hypertension. Evidence also suggests that pregnancy-induced hypertension may result in adverse maternal and child outcomes. The aim of this study was to assess the determinants of pregnancy-induced hypertension among mothers attending antenatal and delivery services at public health hospitals in Wolaita zone, southern Ethiopia. Methods. An institutionally based unmatched case-control study was conducted at three public hospitals. A total of 283 study participants were recruited for this study. Cases were selected consecutively as they were being diagnosed for pregnancy-induced hypertension, and two controls were selected for each case. Data were collected via the face-to-face interview technique using a pretested questionnaire. Unconditional logistic regression analysis was used to identify the independent predictor variables and produced odds ratio (OR) as a measure of association. Results. The mean ± (SD) ages of cases and controls were 26.1 ± 5.4 and 26.1 ± 4.5 years, respectively. Being rural residents (AOR: 2.25, 95% CI: 1.09–4.65), illiterate (AOR: 3.12, 95% CI: 1.20–8.08), having the history of pregnancy-induced hypertension (AOR: 6.62, 95% CI: 2.48–17.71), history of kidney disease (AOR: 3.14, 95% CI: 1.05–9.38), and family history of hypertension (AOR: 5.59, 95% CI: 2.73–11.45) were determinants that increased the odds of suffering from hypertensive disorders of pregnancy. More importantly, eating vegetables and fruit reduces the odds of suffering from pregnancy-induced hypertension by 77% (AOR: 0.23, 95% CI: 0.06–0.79). Conclusion. Being rural residents, illiterate, having a history of pregnancy-induced hypertension, and history of kidney disease, as well as the family history of hypertension were identified determinates of hypertensive disorders of pregnancy in the study area. Furthermore, fruit and vegetable intakes were identified as protective factors for pregnancy-induced hypertension. Therefore, early diagnosis and intervention of this disorder are warranted to reduce adverse outcomes.